2019
DOI: 10.1016/j.cryobiol.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity tests of cryoprotecting agents for Mytilus galloprovincialis (Lamark, 1819) early developmental stages

Abstract: Global aquaculture production of blue mussel has increased over last years. This work reaffirms the great potential of cryopreservation technique on mussel industry and overcome economic barriers a cause of a traditional and rudimentary management and continue growing. The aim of this work is to set some preliminary basis attending to toxicity of cryoprotecting agents (CPAs) on different development stages of Mytilus galloprovincialis as a start point to develop a stable cryopreservation protocol. Toxicity tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Research on other mollusc species like Pacific oyster (Crassostrea gigas) or blue mussel (Mytilus galloprovinciallis) indicate that there is not strong inter-species variability in the response to cryopreservation. In general, EG is the most used CPA for larvae cryopreservation in combination with other non-permeating CPAs like TRE or polyvinylpyrollidone (PVP) [3,6,8,9,16,19,24,25,26,28]. In this study, it was found that higher concentrations of EG, in combination with TRE at a higher concentration and PVP were generally better for survival than lower EG concentrations.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Research on other mollusc species like Pacific oyster (Crassostrea gigas) or blue mussel (Mytilus galloprovinciallis) indicate that there is not strong inter-species variability in the response to cryopreservation. In general, EG is the most used CPA for larvae cryopreservation in combination with other non-permeating CPAs like TRE or polyvinylpyrollidone (PVP) [3,6,8,9,16,19,24,25,26,28]. In this study, it was found that higher concentrations of EG, in combination with TRE at a higher concentration and PVP were generally better for survival than lower EG concentrations.…”
Section: Discussionmentioning
confidence: 80%
“…The final part of this study investigated whether larval performance post-thawing could be improved by freezing larvae at a later stage. It is well known from many previous studies that D-larvae are more resilient to freezing when compared with earlier developmental stages such as trochophore [6,19,20,21,25]. Although, [8] reported that Pacific oysters cryopreserved from a late D-larvae stage (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perna canaliculus D-larvae showed a20% delay in size when compared to controls after 48h incubation post-thaw (Paredes et al 2012, Rusk 2012, Paredes et al 2013, Heres et al 2019.…”
Section: Discussionmentioning
confidence: 93%
“…Crassostrea gigas, followed by C. virginica are the most popular (Paredes 2015). Regarding mussels, sperm cryopreservation is the most reported followed by larvae due to the difficulty of cryopreserving oocytes successfully, described protocols and cryopreservation information for M. galloprovincialis can be found in few reports like Di Mateo et al 2009, Wang et al 2011, Paredes et al 2013, Wang et al 2014or Heres et al 2019.…”
Section: Introductionmentioning
confidence: 99%